Improvement of structural diagrams of vibratory separators with electromagnetic drive - Korendiy, Vitaliy; Shenbor, Vladyslav; Shenbor, Yurii (Видавництво Львівської політехніки, 2017)
The features of construction of structural schemes of vibratory separators based on vibratory conveyors with electromagnetic drive are considered. The structural diagram of the vibratory separator developed on the basis of three-mass oscillatory scheme with the possibility of transporting the mixture and the separated component by vibratory transportation in opposite directions is proposed, and the device operation is substantiated. The main criteria of separation efficiency are presented. The possible directions of effective implementation of vibratory separators are suggested.
Keywords: structural diagram; vibratory separator; armature; electromagnet; vibration angle; elastic system; separation efficiency